Army of mortgagors: Long-run evidence on credit externalities and the housing market - Tobias Herbst; Moritz Kuhn; Farzad Saidi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Houses are the most important asset on American households' balance sheets, rendering the U.S. economy sensitive to house prices. There is a consensus that credit conditions affect house prices, but to what extent remains controversial, as an expansion in credit supply often coincides with changes in house price expectations. To address this longstanding question, we rely on novel microdata on the universe of mortgages guaranteed under the Veterans Administration (VA) loan program. We use the expansion of eligibility of veterans for the VA loan program following the Gulf War to estimate a long-lived effect of credit supply on house prices. We then exploit the segmentation of the conventional mortgage market from program eligibility to link this sustained house price growth to developments in the initially unaffected segment of the credit market. We uncover a net increase in credit for all other residential mortgage applicants that aligns closely with the evolution of house price growth, which supports the view that credit-induced house price shocks are amplified by beliefs.
Keywords: E21; G20; G21; G28; 330; credit supply; mortgages; beliefs; house prices; veterans